2016
DOI: 10.1530/eje-15-0930
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 clinical trial of sunitinib as adjunctive treatment in patients with advanced differentiated thyroid cancer

Abstract: Objective: Our objective was to evaluate the efficacy and safety of sunitinib following at least one course of radioactive iodine treatment in patients with advanced differentiated thyroid cancer (DTC). The study endpoints included best response rate (including best objective response rate) and progression-free survival (PFS) per Response Evaluation Criteria in Solid Tumors (RECIST) 1.1, measurement of serum thyroglobulin (Tg), and toxicity evaluation. Design and methods: This was a single center, nonrandomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Interestingly, a 2010 study of off-label use of both drugs demonstrated the efficacy in patients with widely metastatic, progressive differentiated thyroid cancer [23]. Subsequently, sorafenib was approved by the FDA for the treatment of metastatic differentiated thyroid cancer in 2013, while sunitinib is currently in phase 2 clinical trial as an adjunctive treatment for advanced differentiated thyroid cancer [24]. Moreover, off-label use of sorafenib showed positive results in personalized colon cancer therapy in a number of cases: e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a 2010 study of off-label use of both drugs demonstrated the efficacy in patients with widely metastatic, progressive differentiated thyroid cancer [23]. Subsequently, sorafenib was approved by the FDA for the treatment of metastatic differentiated thyroid cancer in 2013, while sunitinib is currently in phase 2 clinical trial as an adjunctive treatment for advanced differentiated thyroid cancer [24]. Moreover, off-label use of sorafenib showed positive results in personalized colon cancer therapy in a number of cases: e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Among the most advanced investigational compounds, sunitinib (Sutent, SU11248; Pfizer Ltd) has completed phase I and II trials in thyroid cancer (Dawson et al 2008, Carr et al 2010, Atallah et al 2016, Bikas et al 2016, Ravaud et al 2017 and is currently undergoing specific evaluation in RET fusion-positive tumors (NCT02450123). Sunitinib was part of a large indolinone compound collection at SUGEN Inc (later acquired by Pfizer), which was initially developed to block angiogenic kinases belonging to the split tyrosine kinase domain family (VEGFR, FGFR, PDGFR) (Sun et al 1998(Sun et al , 1999(Sun et al , 2000.…”
Section: Investigational Drugsmentioning
confidence: 99%
“…sunitinib) and/or bisphosphonates, amongst others (Najjar & Finke 2013). Notably, sunitinib has recently demonstrated anti-tumor activity in advanced differentiated thyroid cancer (Bikas et al 2016). Although the benefit seen with sunitinib treatment has not been definitively attributed to MDSC depletion, it is known to augment MDSCs, which correlates with enhanced tumor-specific responses generated by cancer vaccines in preclinical models (Wesolowski et al 2013).…”
Section: Myeloid Cellsmentioning
confidence: 99%